Genetic Diversity and Phylogenetic Analyses of Turkish Cotton (Gossypium hirsutum L.) Lines using ISSR Markers and Chloroplast trnL-F Regions. Issue 5 (4th May 2022) - Hocaoglu-Ozyigit, Asli; Ucar, Bihter; Altay, Volkan; Ozyigit, Ibrahim Ilker
ABSTRACT: In this study, genetic diversity and phylogenetic relationships of 22 cotton ( Gossypium hirsutum L.) lines widely cultivated in Turkey were investigated. For this purpose, 20 ISSR primers were used, and five of which generated amplification products. The polymorphic locus ratio was calculated as 87.21% and a moderate level of genetic diversity was found between the genotypes. Percentage of the highest polymorphic locus was calculated as 12.79% for the Beren line, whereas ADN 98, ADN 710, and Özbek 105 lines showed the lowest value with 0.00%. trnL-F intergenic spacer sequences were used in order to determine phylogenetic relationships, and a comparison was carried out between both sequences of our lines and the sequences obtained from NCBI-GenBank database. The sequences of G. hirsutum, G. hirsutum subsp. latifolium, and G. hirsutum cv. "Hainansijimian" were described as the most similar sequences according to specifications of coverage, similarity, and maximum score ranges. Then, a phylogenetic tree was established by using the sample sequences from the prominent families cultivated, especially from Malvaceae. While the members of Malvaceae family were clustered as one group, the other families were comprised of different groups located in different positions according to their genetic similarities.